Kilka uwag na temat nauk historycznych w klasyfikacji Kazimierza Ajdukiewicza - Bigaj, Jan (Filozofia Nauki, 2002)
History is hardly ever classified not as the science about the past of the human race. Meanwhile, fairly big part of it is due to nonhumanistic sciences like paleontology, geology or cosmogony. Thus, it would be reasonable to classify history by methodology rather, common to the mentioned sciences, that allows to reconstruct the past on the grounds of various kinds of traces